Targeting Non-coding RNA for Glioblastoma Therapy: The Challenge of Overcomes the Blood-Brain Barrier - Sharma, Rohit K.; Calderon, Carlos; Vivas-Mejia, Pablo E. (Frontiers in Medical Technology, 2021)
Glioblastoma (GBM) is the most malignant form of all primary brain tumors, and it is responsible for around 200,000 deaths each year worldwide. The standard therapy for GBM treatment includes surgical resection followed by temozolomide-based chemotherapy and/or radiotherapy. With this treatment, the median survival rate of GBM patients is only 15 months after its initial diagnosis. Therefore, novel and better treatment modalities for GBM treatment are urgently needed. Mounting evidence indicates that non-coding RNAs (ncRNAs) have critical roles as regulators of gene expression. Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) are among the most studied ncRNAs in health and disease. Dysregulation of ncRNAs is observed in virtually all tumor types, including GBMs. Several dysregulated miRNAs and lncRNAs have been identified in GBM cell lines and GBM tumor samples. Some of them have been proposed as diagnostic and prognostic markers, and as targets for GBM treatment. Most ncRNA-based therapies use oligonucleotide RNA molecules which are normally of short life in circulation. Nanoparticles (NPs) have been designed to increase the half-life of oligonucleotide RNAs. An additional challenge faced not only by RNA oligonucleotides but for therapies designed for brain-related conditions, is the presence of the blood-brain barrier (BBB). The BBB is the anatomical barrier that protects the brain from undesirable agents. Although some NPs have been derivatized at their surface to cross the BBB, optimal NPs to deliver oligonucleotide RNA into GBM cells in the brain are currently unavailable. In this review, we describe first the current treatments for GBM therapy. Next, we discuss the most relevant miRNAs and lncRNAs suggested as targets for GBM therapy. Then, we compare the current drug delivery systems (nanocarriers/NPs) for RNA oligonucleotide delivery, the challenges faced to send drugs through the BBB, and the strategies to overcome this barrier. Finally, we categorize the critical points where research should be the focus in order to design optimal NPs for drug delivery into the brain; and thus move the Oligonucleotide RNA-based therapies from the bench to the clinical setting.